FUNGSI GUA SOLO OTI DI DESA TAIPA KECAMATAN LEMBO KABUPATEN KONAWE UTARA - Ratnasari Ratnasari; abdul alim (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
Prehistory is an are where humans do not know writing, so that the conditions and events experienced by humans at that time cannot be learned throungh writing. Solo Oti Cave is a prehistoric cave that can still be observed archeologically this cave is located in the Taipa village area, Lembo District, Konawe Utara Regency.The objectives of this study are to discover the remained relics in to Solo Oti cave end to know the fuction of the Solo Oti based on its found relics.The research questions of this paper are, first, what are the archaeological relics that found in the Solo Oti cave. Second, how the functions of the Solo Oti cave based on those relics. This paper uses cultural history theory that focuses on descriptive research methods in answering research problems. The results showed that the archaeological remains found in the Oti Solo Cave, were 10 potteries provided included 4 potteries which had plain motives and 6 potteries which had decorative motives. There are also 9 findings of human fragments namely thigh bone, shin bone, cubit bone, forehead bone, arm bone, back of the head bone, lower jaw bone, irregular bone, and neck bone. Additionally, there are 14 findings of human teeth namely 4 upper molar stop, 3 lower molars, 2 incisors, 1 canine tooth, and 4 initial premolar teeth. Meanwhile, theOti Solo Cave function is remains is functioned as a burial cave.